2018
DOI: 10.1186/s12866-018-1179-7
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variability in the sdrD gene in Staphylococcus aureus from healthy nasal carriers

Abstract: BackgroundStaphylococcus aureus cell wall anchored Serine Aspartate repeat containing protein D (SdrD) is a member of the microbial surface component recognising adhesive matrix molecules (MSCRAMMs). It is involved in the bacterial adhesion and virulence. However the extent of genetic variation in S. aureus sdrD gene within isolates from healthy carriers are not known. The aim of this study was to evaluate allelic variation of the sdrD gene among S. aureus from healthy nasal carriers.ResultsThe sdrD A region f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 50 publications
0
15
1
Order By: Relevance
“…All ST338 isolates as well as ST59-SCCmec Vb strains harboured similar virulence factors and genomic islands; however, the former lacked the clfA, clfB, ebp, cna, sdrC, and sdrD genes found in MW2 and USA300. ClfA promotes bacterial colonization and adhesion [45]; clfB, sdrC, and sdrD mediate adhesion to human nasal mucosa [46][47][48]; and Cna is involved in tissue colonization [49]. Experiments in mice and human alveolar epithelial cells showed that ST338 had a lower nasal colonization capacity than MW2, which is consistent with its lack of adhesion factor genes (clfA, clfB, ebp, sdrC, and sdrD).…”
Section: Discussionmentioning
confidence: 79%
“…All ST338 isolates as well as ST59-SCCmec Vb strains harboured similar virulence factors and genomic islands; however, the former lacked the clfA, clfB, ebp, cna, sdrC, and sdrD genes found in MW2 and USA300. ClfA promotes bacterial colonization and adhesion [45]; clfB, sdrC, and sdrD mediate adhesion to human nasal mucosa [46][47][48]; and Cna is involved in tissue colonization [49]. Experiments in mice and human alveolar epithelial cells showed that ST338 had a lower nasal colonization capacity than MW2, which is consistent with its lack of adhesion factor genes (clfA, clfB, ebp, sdrC, and sdrD).…”
Section: Discussionmentioning
confidence: 79%
“…To our knowledge, such recombination has not been previously reported in S. aureus. While it is known that serine-aspartate repeat MSCRAMM proteins are variable and contribute to biofilm formation [93,94], more work needs to be done to characterise the relationship between divergent serine-aspartate repeat MSCRAMM proteins and their relationship to within-host adaptation.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, such recombination has not been previously reported in S. aureus . While it is known that serine-aspartate repeat MSCRAMM proteins are variable and contribute to biofilm formation (Ajayi et al, 2018; Barbu, Mackenzie, Foster, & Hook, 2014), more work needs to be done to characterise the relationship between divergent serine-aspartate repeat MSCRAMM proteins and their relationship to within-host adaptation.…”
Section: Discussionmentioning
confidence: 99%